Introducing multiple-choice questions to promote learning for medical students: effect on exam performance in obstetrics and gynecology - Jud, Sebastian; Cupisti, Susanne; Frobenius, Wolfgang; Winkler, Andrea; Schultheis, Franziska; Antoniadis, Sophia; Beckmann, Matthias; Heindl, Felix (Archives of Gynecology and Obstetrics, 2020)
Purpose: Testing is required in medical education. The large number of exams that students face requires effective learning strategies. Various methods of improving knowledge retention and recall have been discussed, two of the most widely evaluated of which are test-enhanced learning and pause procedures. This study investigated the effect of voluntary multiple-choice questions on students’ performance. Methods: In a prospective study from April 2013 to March 2015, 721 students were randomly assigned to receive supplementary online material only (control group) or additional multiple-choice questions (investigative group) accompanying lectures. Their performance in the final exam was evaluated. Results: A total of 675 students were ultimately included, with 299 randomly assigned to the investigative group and 376 to the control group. Students in the investigative group scored significantly better in relation to grades and points (2.11 vs. 2.49; 33 vs 31.31; p < 0.05). The effect declined over time. Conclusion: This is the first study of the use of voluntary multiple-choice questions to improve medical students’ performance. The results support test-enhanced learning and the feasibility of implementing multiple-choice questions in lectures.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Gynecology; Lecture; Multiple choice; Obstetrics; Teaching; Testing